Дослідження посаду літописного городища Жидичин у 2009 р. - Златогорський, О.Є.; Баюк, В.Г. (Археологічні дослідження в Україні, 2010)
In 2009, at «posad» (trading quarter) of a mentioned in chronicle Zhydychyn hill-fort an area of 84 m2 to the south-east from the St. Mykola Monastery was excavated. A husbandry pit of the Early Slavic period, a cultural layers of Pomorska culture, of the Ancient Rus period of the 10th and 11th c., and of the Late Mediaeval period were uncovered. It is stated, that in the Ancient Rus period the settlement belonged to the northern suburbs of Luchesk.